GRAND STRATEGY GUNA MEWUJUDKAN KEINGINAN PENGEMBANGAN WILAYAH TAPAL KUDA MENJADI KESATUAN DAERAH PERENCANAAN DI ERA OTONOMI DAERAH - Rokhani Rokhani; Agus Supriono; Djoko Soejono (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2011)
Alternative of policy model that can be considered to be effective and efficient in order to ‘make synergy’ of interests in actualizing the desire for unity of Horse Shoe area into one unit of regional planning under the importance of regional autonomy policy implementation is by integrated economic development of reliable zone on specific of locality base. The next is question about what are internal and external factors that can be considered to be potentially covering, and also how the grand strategy in the frame of actualizing those desire. In order to answer this question, there was approach of evaluation matrix analysis of internal and external factors as well as grand strategy of SWOT interaction. Based on the research result, it can be found out that there are 10 (Ten) factors of internal strength, 8 (eight) factor of internal weaknesses, 3 (three) external opportunity, and 4 (four) external threat that has covering potential. The existence of supporting potential in order to actualize this desire is internally under strong position and externally can be effective in utilizing the opportunity as well as minimizing the negative effect of external threat potential. Grand Strategy in order to actualize this desire is by SO strategy. It means that the potential of superiority being owned, namely factors of internal should be well-managed so that this can be as trigger strength (triger/move of rule) in order to obtain existing opportunities. Key words : grand strategy, regional planning, Horse Shoe Area, decentralization